A detailed analysis of cross-phase modulation effects on OOK and dpsk optical WDM transmission systems in the presence of GVD, SPM, and ASE noise - Abbou, F. M.; Hiew, C. C.; Chuah, Hean Teik; Ong, Duu Sheng; Abid, A. (Springer, 2008)
A performance analysis is carried out to evaluate the effect of cross-phase modulation (XPM) on a dispersion-managed 20 Gb/s optical wavelength-division multiplexing (WDM) transmission system using either the on-off keying (OOK) or the different-phase-shifting keying (DPSK) modulation, in the presence of the group-velocity dispersion (GVD), self-phase modulation (SPM), and amplified spontaneous emission (ASE). It is found that to achieve a bit error rate (BER) of 10(-9) at a distance of 160 km, a 1.0 dB XPM power penalty is incurred for input channel power of 3 dBm in the OOK transmission and 7 dBm in the DPSK transmission. The power penalty increases with input channel powers and is inversely proportional and exhibits oscillations with respect to the channel separation. The oscillation is evenly spaced for the DPSK but not for the OOK and suggests the presence of optimum separation values. The XPM penalty decreases when a high dispersion filer is used and increases linearly with increasing dispersion slope. Small residual dispersion can reduce the penalty of nonlinear effects.